Penegakan Hukum atas Tindak Pidana Pencurian oleh Pengidap Kleptomania (Studi Putusan Nomor 32/Pid.B/2018/PN Kpg dan 574/Pid.B/2019/PN.Dps) - Lorenza Ainun Merdekawati; Hartiwiningsih; Anita Zulfiani (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
Kleptomania is a disorder of habit and impulse that drives sufferers to steal compulsively, not for economic motives. This condition creates significant legal complexities, particularly in applying criminal liability as regulated under Article 44 of the Criminal Code regarding grounds for exemption from punishment. This study aims to analyze law enforcement regarding theft crimes committed by kleptomaniacs in Indonesia and to identify obstacles encountered in the enforcement process. This research employs a normative legal method using statutory and case approaches, examining two court decisions: Decision Number 32/Pid.B/2018/PN Kpg and Decision Number 574/Pid.B/2019/PN.Dps. The results indicate inconsistency in law enforcement against theft perpetrators who suffer from kleptomania. The first decision adopted a rehabilitative approach by mandating psychiatric treatment, while the second was more retributive without a rehabilitation order. Identified obstacles include weak legal substance, complexity of clinical proof, stigma against mental disorders in legal culture, and philosophical tension between punishment and medical rehabilitation needs.